2016
DOI: 10.33549/physiolres.933266
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alfacalcidiol and Metformin on Phenotype Manifestations in Women with Polycystic Ovary Syndrome – a Preliminary Study

Abstract: Aim of this study was to evaluate the effect of vitamin D supplementation in obese, insulin resistant and vitamin D deficient PCOS women on biochemical and clinical hyperandrogenism and menstrual irregularity in comparison to effect of metformin or combined metformin plus vitamin D therapy. Thirty nine PCOS women were randomized into three groups and treated with alfacalcidiol (Group 1), combined alfacalcidiol and metformin therapy (Group 2) and metformin (Group 3) for 6 months. Serum TST, fTST, DHEAS, LH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 17 publications
0
26
0
4
Order By: Relevance
“…Nine studies were included in the present meta‐analysis which investigated the impact of vitamin D supplementation in 647 patients . The actual number of patients that were randomised in the various treatment groups is available in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were included in the present meta‐analysis which investigated the impact of vitamin D supplementation in 647 patients . The actual number of patients that were randomised in the various treatment groups is available in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies investigated the impact of vitamin D on acne and hirsutism with conflicting evidence . Evidence regarding its action on menstrual cycle regularity remain also inconclusive …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vitamin D and calcium co-supplementation in PCOS women could result in a better outcome in a variety of PCOS symptoms, such as menstrual regularity, and ovulation [ 23 ]. However, vitamin D supplementation for 6 months among obese vitamin D-deficient PCOS women had no significant effect on androgen levels and clinical features of hyperandrogenism [ 24 ]. In addition, two meta-analysis studies conducted by He et al [ 8 ] and Xue et al [ 9 ] demonstrated no evidence that vitamin D intake reduced or mitigated metabolic and hormonal profiles in PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…We became interested in understanding vitamin D's influence on androgens because polycystic ovary syndrome (PCOS) is simultaneously the most common endocrinopathy in women worldwide (18)-specifically causing hyperandrogenism specifically-and the most common cause of ovulatory dysfunction (19). One small study of normal-BMI PCOS patients and healthy, non-obese women demonstrated a positive relationship between vitamin D and total testosterone (TT) (20) while another similar study found no relationship (21). Results among postmenopausal women show a negative relationship between vitamin D and TT (22,23).…”
Section: Vitamin D and Androgensmentioning
confidence: 99%